2007
DOI: 10.1093/bja/ael342
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with controlled-release oxycodone does not improve management of postoperative pain after day-case gynaecological laparoscopic surgery

Abstract: Oral premedication with CR oxycodone did not improve management of postoperative pain after day-case gynaecological laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
2
18
1
1
Order By: Relevance
“…Results of our study are similar to those by Jokela et al 9 These authors also found no improvement in postoperative pain scores after pre-medication with 15 mg of oxycodone CR in day-case gynaecological laparoscopic surgery patients. This is in contrast to a similar study by Reuben et al 8 who showed a reduction in the consumption of rescue pain analgesics, VAS scores, incidence of All authors contributed to conception and design, manuscript preparation, read and approved the final manuscript.…”
Section: Discussionsupporting
confidence: 91%
“…Results of our study are similar to those by Jokela et al 9 These authors also found no improvement in postoperative pain scores after pre-medication with 15 mg of oxycodone CR in day-case gynaecological laparoscopic surgery patients. This is in contrast to a similar study by Reuben et al 8 who showed a reduction in the consumption of rescue pain analgesics, VAS scores, incidence of All authors contributed to conception and design, manuscript preparation, read and approved the final manuscript.…”
Section: Discussionsupporting
confidence: 91%
“…The standard deviation (SD) in the reference study [12] was 1.3 in the placebo group at this time point. The minimal target difference (TD) with clinical significance is 1 point of VAS.…”
Section: Discussionmentioning
confidence: 87%
“…Sample size calculation was based on a visual analogue score (VAS) for pain at rest calculated in the reference study [12] in the first hour after the end of anesthesia. The standard deviation (SD) in the reference study [12] was 1.3 in the placebo group at this time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher frequency of constipation in that study can be explained by the time of opioid use, which was longer than in our study, limited to two days. Jokela et al studied premedication with 15 mg controlled-release oxycodone in gynecological laparoscopic operations and found 25% of nausea and vomiting 17 . The higher frequency could be explained by the different type of operation, since the gynecological laparoscopic operations may cause a higher incidence of nausea and vomiting compared with head and neck procedures.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%